[Hillside Farms and Waterfalls Near Laki Fissure] - Streng, Evelyn Fiedler (1975)
Photograph of hillside farms and waterfalls near the Laki Fissure. Green plateaus and hills surround small farms dotted along the flat plains at the center of the photograph. A grey, watery, lowered section of the land cuts through the bottom half of the photograph, a grey, stone road leading to it from the bottom right corner of the photograph. A wall of white clouds covers the top of the photograph, obscuring hills behind it.